"DECIDING RIGHT" PROJECT, RIGHT CARE, RIGHT PLAN FOR RIGHT PATIENT. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Than, Tun; Adam, Zahida; Wadhhwa, Preeti; Ayubi, Mohamed
Abstract : Aims and Objectives: Although healthcare professionals perceive palliative care as a rewarding humane work, lack of training, leadership and resources are often cited as impediments to deliver high quality palliative care services. Recognising these hurdles and the scope for improvement in palliative care services across Leicester city, the commissioning group, the local hospice (LOROS) and Macmillan Cancer Support collaborated in launching an innovative "Deciding Right" project. This aims to promote identification of patients in their last year of life to provide a timely and robust multidisciplinary care based on the patient's choices. Description of the Project: The highlights of the project include developing a local enhanced service (LES), appointing and training of four locality GP mentors to promote awareness, sign-post and support various local health professionals and pathway mapping with multidisciplinary organizations to establish an integrated palliative care services. The service specification of the LES focused on developing and training a palliative care lead GP for each participating practice, timely identification of patients suitable for the care plan, effective discussion with the patients, families and the multidisciplinary team to develop and implement the plan in collaboration, systematic recording of the care plan on the novel, purpose-built and user friendly template on System One, and reflective learning for further development through after-death-audits (ADA). Results and reflections: Each practice in the city now has a palliative care lead GP who has received training in identification of patients in their last year of life, communication and care planning. The project achieved improvements in the palliative care register across the city along with paving the pathway to provide an excellence in palliative care through effective communication across multidisciplinary team. It also highlight the need for more comprehensive guidelines for anticipatory prescribing and co-ordination of palliative care in out of hours settings.